U.S. Pavilion Interior Courtyard (Seville Enterprises, Inc.)
U.S. Pavilion, spread under a sweeping translucent canopy that would cover nearly two football fields. It is supported by a network of more than four and a half miles of steel cables that together with the steel mast weigh about 200 tons.